Neurotoxin injection in benign submandibular gland hypertrophy: A first choice treatment. Issue 2 (17th February 2020) - Karapantzou, Chrisanthi; Jakob, Mark; Canis, Martin
Abstract: Background: Various benign clinical entities with a symptomatology of hypertrophic submandibular glands like sialadenitis, sialadenosis, sialolithiasis, or an ageing neck have been described. Botulinum toxin type A is an elegant tool in the management of these conditions. Methods: This article is an original article, describing the Munich Concept of treating persistent submandibular swelling with Botulinum Toxin Type A from aesthetic and functional aspect. To shrink the affected tissue, 15 Units of Botox or Xeomin are applied in a single injection technique and under ultrasound guidance into the glands. Therefore, the 100 Units vial is being diluted with 3.5 of NaCl. Results: Intraglandular injections, using a specific dilution and dosage of the neurotoxin preparations, are very effective in the management of these swellings, offering safe and long‐lasting results, with a high satisfaction rate. Our working group treated in the last 18 months 23 patients with benign, bilateral submandibular gland hypertrophies, which did not have any major complications. Conclusion: As there is not yet described an ideal therapeutic strategy for the management of this symptomatology, we suggest, based on our experience, a concept with very promising results from functional and cosmetic aspect.